A Business System Model as a Basis for the Establishment of a Digital Twin (Vloga naprednih tehnologij v inženiringu poslovnih sistemov, 2025)
In the research, we addressed the problem of understanding the functioning of business systems and managing changes in business systems. We focused on the challenges of understanding and managing business processes in real-time. In the theoretical part of the research, we found that one of the technologies that enable the understanding and control of business processes in real-time is the so-called digital twin. We were interested in whether it is possible to use the already created business repository of the selected business system as a basis for creating a digital twin. We were interested in which additional technologies are needed to design and use a digital twin and which key process indicators make sense to monitor during use. Finally, we were interested in how much effort and time is required to create a digital twin and where the user encounters obstacles. We found that using digital twins is promising, but development is still in its early stages. Further research and application development will be required to make the technology suitable for widespread use in a business environment.